Text-to-image artificial intelligence to understand astronaut visual phenomena during spaceflight - Ethan Waisberg; Joshua Ong; Mouayad Masalkhi; Nasif Zaman; Andrew G Lee; Alireza Tavakkoli (The Pan-American Journal of Ophthalmology, 2023)
Astronauts have documented visual phenomena during spaceflight. However, given that these are only experienced by the astronaut themselves, these unique neuro-ophthalmic visual phenomena occur while in space which remain poorly understood by nonastronauts. There are various risks to the neuro-ophthalmic system in space including spaceflight-associated neuro-ocular syndrome and galactic cosmic radiation, and thus, further understanding what astronauts are experiencing is of critical importance. In this study, we employ artificial intelligence (AI) text-to-image AI frameworks to descriptions of visual phenomena experienced during spaceflight to further understand phosphenes and oscillopsia in space motion sickness. Building upon this technology may help researchers and clinicians to further understand how the spaceflight environment impacts the neuro-ophthalmic system.